2013
DOI: 10.1074/jbc.m112.421057
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Trypanosome Cyclophilin Inactivates Lytic Insect Defense Peptides and Induces Parasite Calcineurin Activation and Infectivity

Abstract: Background:The mechanisms of insect immune peptide recognition and evasion by T. cruzi are unknown. Results: Secreted parasite cyclophilin neutralizes lytic peptide, causes activation of parasite calcineurin, and enhances parasite infection. Conclusion: Cyclophilin is a key mediator of antimicrobial peptide evasion and triggers parasite calcineurin signaling. Significance: The cyclophilin-calcineurin pathway is an extracellular peptide microbial-host sensing mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 61 publications
2
26
0
2
Order By: Relevance
“…In contrast, rdEpi is resistant to the human complement system, interacts with macrophages in a similar manner to trypomastigotes (even though it does not exhibit the amastigote intracellular stage) and can also infect mice. Some recent data corroborate the notion that epimastigotes could be infective in vitro to mammalian cells (Kulkarni et al, 2013), but the present work is the first to shows the genesis of epimastigote forms that maintain infectivity even after several duplication cycles. Some could argue against the present data that rdEpi is simply a transitional stage in the differentiation of trypomastigotes to epimastigotes, which could explain its virulence.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, rdEpi is resistant to the human complement system, interacts with macrophages in a similar manner to trypomastigotes (even though it does not exhibit the amastigote intracellular stage) and can also infect mice. Some recent data corroborate the notion that epimastigotes could be infective in vitro to mammalian cells (Kulkarni et al, 2013), but the present work is the first to shows the genesis of epimastigote forms that maintain infectivity even after several duplication cycles. Some could argue against the present data that rdEpi is simply a transitional stage in the differentiation of trypomastigotes to epimastigotes, which could explain its virulence.…”
Section: Discussionsupporting
confidence: 89%
“…PP2B is involved in a number of different signaling pathways and so participates in some physical activities. In Trypanosoma , Cyclophilin–trialysin synergistically acts on parasites to activate calcineurin phosphatase signaling, which mediates cAMP recognition and evasion and adaptation of the parasite . Orrego et al .…”
Section: Introductionmentioning
confidence: 99%
“…The authors were also able to show that Cyp19 and P6 in concert are able to activate the calcium-dependent phosphatase calcineurin, by an as yet unknown mechanism, and thereby increase the infectivity of the parasites. Moreover, the activating and protective effects of the Cyp19-P6 complex could be transferred successfully to L. major and Leishmania amazonensis strains when conditioned medium of either species was used, indicating that these are general virulence mechanisms of trypanosomatid parasites (163). It is still an open question whether the binding of Cyp19 to P6 or other proline-containing CAMPs resembles a simple receptor-ligand interaction mediated by a proline residue or whether the PPIase activity contributes to neutralization of P6 by isomerizing it from an active to an inactive form.…”
Section: Protozoan Ppiases In Virulencementioning
confidence: 96%
“…In a recent study, it was shown that cationic antimicrobial peptides (CAMPs), part of the innate defense system of the reduviid bug vector of T. cruzi, can stimulate this transition rather than having an antiparasitic action. Intriguingly, this activation is dependent on the presence of the secreted cyclophilin Cyp19 of the parasite (163). For their study, the authors focused on the model CAMP P6, which is the biologically active N-terminal part of trialysin of Triatoma infestans.…”
Section: Protozoan Ppiases In Virulencementioning
confidence: 99%